1997
DOI: 10.1016/s0009-9236(97)90102-8
|View full text |Cite
|
Sign up to set email alerts
|

Fenoterol but not dobutamine increases erythropoietin production in humans

Abstract: This study shows in a model of controlled, physiologic stimulation of renal erythropoietin production that the beta 2-adrenergic receptor agonist fenoterol but not the beta 1-adrenergic receptor agonist dobutamine is able to increase erythropoietin levels in humans. The result can be interpreted as a hint that signals for the control of erythropoietin production may be mediated by beta 2-adrenergic receptors rather than by beta 1-adrenergic receptors. It appears to be unlikely that an increase of renin concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
36
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(43 citation statements)
references
References 19 publications
6
36
1
Order By: Relevance
“…We have shown that theophylline [5,6] and fenoterol [7] increase the EPO concentration in humans after a controlled haemorrhage compared to placebo treatment. We have shown that theophylline [5,6] and fenoterol [7] increase the EPO concentration in humans after a controlled haemorrhage compared to placebo treatment.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…We have shown that theophylline [5,6] and fenoterol [7] increase the EPO concentration in humans after a controlled haemorrhage compared to placebo treatment. We have shown that theophylline [5,6] and fenoterol [7] increase the EPO concentration in humans after a controlled haemorrhage compared to placebo treatment.…”
Section: Introductionmentioning
confidence: 89%
“…As in earlier studies [2,5,6,7] the following commercially available assay kits were used. EPO in plasma was analysed using a monoclonal enzyme-linked immunosorbent assay (ELISA, catalogue number 500, Medac, Hamburg, Germany), PRA was measured with a radioimmunoassay kit for angiotensin I [ 125 I]RIA (RENK P2510, Sorin Biomedica, Saluggia, Italy), and A II in plasma was determined using a radioimmunoassay (number 40-6005, Nichols Institute Diagnostics, San Juan Capistrano, USA).…”
Section: Methodsmentioning
confidence: 99%
“…As in earlier studies [4][5][6][7]18], the following commercially available assay kits were used. Epo in plasma was analysed using a monoclonal enzyme-linked immunosorbent assay (ELISA, catalogue no.…”
Section: Methodsmentioning
confidence: 99%
“…In systematic examinations we have shown that theophylline increases Epo concentrations in humans after a controlled stimulus with haemorrhage [4][5][6]. These findings may be interpreted as an indirect effect, via the increase of plasma renin activity (PRA) with a subsequent increase of AII levels as it occurs during theophylline infusion.…”
Section: Introductionmentioning
confidence: 95%
“…However, Jelkmann et al (1979) could not confirm these findings, since his group reported unchanged EPO levels following long-term administration of a selective ␤2-adrenergic agonist in rabbits (Jelkmann et al, 1979). Studies in humans showed that EPO secretion was higher following administration of fenoterol, a ␤2-adrenergic receptor agonist following hemorrhage and under normoxic conditions (Gleiter et al, 1997(Gleiter et al, , 1998Freudenthaler et al, 1999a).…”
mentioning
confidence: 99%